Gênese e evolução do depósito arqueano aurífero Lamego: mapeamento litoestrutural, modelamento 3D, geocronologia, paragênese mineral, mapas químicos e ablação a laser em sulfetos - Breno de Souza Martins (2016)
The Lamego orogenic gold deposit (1.3 million t ore resources at 4.26 g/t Au) is located at the north-east portion of the Quadrilátero Ferrífero region, Brazil, hosted in the Archean Rio das Velhas greenstone belt. The lithological succession at Lamego consists of metamorphosed (greenschist facies) mafic volcanic rock, chert and banded iron formation (BIF), carbonaceous and micaceous pelites. The Lamego fold controls the deposit, and is the most visible structure related to the D1-D2 event, having a perimeter of about 4.8 km and a maximum width of 450 m. The fold is defined by the layering of the mafic unit with minor BIF and large exposures of carbonaceous and micaceous pelites. It is a rootless, reclined, isoclinal, cylindrical fold with an axial trace striking NW-SE dipping 20º to 30º. The hinge zone is thickened and the limbs are thinned, with the limbs dipping 20º to 30º to the SE. Orebodies include (i) the Lamego BIF (carbonate, +magnetite, chert, carbonaceous matter), where mineralization is related to sulfide-rich bands, and (ii) silicification zones, containing free gold. The BIF is dominated by replacement-style mineralization where sulfides replace carbonate, and are mainly pyrite, As-rich pyrite, and arsenopyrite. Two structural generations, G1 and G2, are recognized and encompass a set of structural elements. The generation G1 developed in a progressive deformation event and resulted in structures oriented from NE-SW, dipping to the SE. Structures pertaining to the G2 structural generation are oriented N-S dipping to the W. The four major high-grade gold orebodies are Carruagem, Queimada, Arco da Velha, and Cabeça de Pedra. Their gold grade shows a spheroidal pattern and a distribution that varies along the S1-2 foliation. These lenses represent the hinge zone of F2 reclined folds with the plunge of the orebodies controlled by the F2 fold axes. The lower-grade gold lenses are controlled by pinch and swell, and locally quartz boudins developed during D1-2. They have two orthogonal directions, one to the NW-SE and the other to the NE-SW, thereby defining chocolate-tablet style boudinage. Paragenetic studies based on texture and elemental mapping with EPMA define seven pyrite types, four in carbonaceous pelite (CP), Py-1CP (framboidal) to Py-4CP, and three in BIF, Py-1BIF to Py-3BIF, as well as Apy-1BIF. These studies establish four stages of evolution: (1) pre-hydrothermal (diagenetic) Py-1CP and its recrystallization to Py-2CP, (2) early hydrothermal additional Py-2CP; development of Py-3CP and Py-1BIF showing S-As-Fe zoning, (3) main hydrothermal additional Py-3CP, development of Py-4CP and Py-2BIF, and (4) late hydrothermal Py-4CP, Py-3BIF showing Ni-Co-As zoning, and Apy-1BIF.